Hot melt adhesive comprising a butene-1 polymer and exhibiting
Through the isotactic and isotactic polymer blend of butene-1, the processing difficulties of hot melt adhesives and the stratification of low molecular weight components on high-speed production lines are solved, and high efficiency processability and stability.
Patent Information
- Application Number
- CN202380044061.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-04
- Filing Date
- 2023-03-30
- Publication Date
- 2025-01-14
AI Technical Summary
Existing hot melt adhesives are difficult to process on high-speed industrial production lines, and contain a high proportion of low molecular weight components that are easily stratified and oozed, resulting in changes in properties and potential skin irritation problems.
Using a hot melt adhesive made of a blend of non-isotactic and isotactic polymers of butene-1, the melt viscosity is reduced and crystallization characteristics are optimized by adjusting the ratio and polydispersion index of the polymer. , reduce the use of low molecular weight components.
It achieves good processability and cohesion on high-speed production lines, while reducing the layering and exudation of low molecular weight components, and improving the stability and safety of the adhesive.
Smart Images

Figure BDA0005161645330000211 
Figure BDA0005161645330000231 
Figure BDA0005161645330000241
Abstract
Description
Technical Field
[0001] The present invention discloses a new hot melt adhesive formulation comprising a blend of at least two polymers of butene-1 as its main polymer component. The at least two polymers differ from each other at least in certain properties, which are primarily (but not exclusively) related to their most important thermal properties. In particular, the hot melt adhesive of the present invention comprises a polymer blend formed by mixing at least two polymers of butene-1 A) and B) in an appropriate and balanced ratio, wherein the polymers are characterized in that:
[0002] A) The polymer A) is a butene-1 non-isotactic copolymer having a unimodal composition, a polydispersity index Mw / Mn of not less than 3.5 and consisting of butene-1 copolymerized with one or more α-olefins selected from ethylene, propylene and C5 to C12 α-olefins. The polymer A) has a content of one or more comonomers of not less than 20 mol% and is also characterized by the following thermal properties measured by DSC after aging for five days under room conditions (23°C and 50% relative humidity):
[0003] - a melting enthalpy of not more than 40 J / g, preferably not more than 35 J / g and more preferably not more than 30 J / g;
[0004] - Peak melting temperature is not higher than 80°C;
[0005] - Glass transition temperature Tg is not higher than -10°C;
[0006] B) Polymer B) is an isotactic butene-1 polymer composition having a global polydispersity index Mw / Mn of less than 3.5 and having a bimodal composition. In fact, it is formed by two butene-1 polymers B1) and B2), each of which has a single polydispersity index Mw / Mn of less than 3.5 and will be described in more detail below. The total content of copolymerized comonomers of the isotactic butene-1 polymer composition is less than 20 mol%; the comonomers are selected from ethylene, propylene and α-olefins having a carbon number equal to or greater than 5. In addition, the isotactic butene-1 polymer composition is characterized by the following thermal properties measured by DSC after aging for five days under room conditions:
[0007] - a melting enthalpy greater than 20 J / g, preferably greater than 25 J / g and more preferably greater than 30 J / g;
[0008] - Peak melting temperature above 90°C;
[0009] - The glass transition temperature Tg is not higher than -20°C.
[0010] Said isotactic butene-1 polymer compositions B) having a bimodal composition can be produced in two separate and distinct synthesis steps, within the production reactor itself, during the polymerization step; or, on the contrary, they can also be produced by mechanically blending on a submicroscopic scale two butene-1 polymers, which are synthesized separately and subsequently intimately blended in the molten or solution state.
[0011] In yet another embodiment of the present invention, the hot melt adhesive disclosed herein comprises 5 wt % to 99.5 wt % of the polymer, preferably 60 wt % to 99.5 wt % of the polymer.
[0012] In another embodiment, the hot melt adhesive of the present invention contains no more than 35% by weight, preferably no more than 25% by weight, even more preferably no more than 15% by weight of low molecular weight components, in particular the sum of tackifying resins plus viscosity modifiers plus waxes. As an example, the average molecular weight Mn of most of these low molecular weight components is usually no more than 2500 g / mol, usually no more than 1500 g / mol, and often less than 1000 g / mol.
[0013] In a third embodiment, the weight ratio of polymer A) (i.e., a butene-1 non-isotactic copolymer having a unimodal composition and a polydispersity index of not less than 3.5) and polymer B) (i.e., a butene-1 isotactic polymer composition having a bimodal composition and a polydispersity index of less than 3.5) is greater than 1. The combination between isotactic and non-isotactic polymers of butene-1 having different polydispersity indices, different global comonomer contents and different thermal properties provides novel hot melt adhesives with an unexpected combination of strong adhesion even on difficult-to-bond substrates such as plastic films, and high cohesion and mechanical properties, especially after aging of these adhesives in the solid state.
[0014] The hot melt adhesive according to the invention also exhibits excellent processability even on industrial production lines running at high or very high speeds (eg equal to or greater than 200 m / min), such as for example those used for the manufacture of absorbent hygiene articles.
[0015] definition
[0016] "Comprising" or "which includes" is used herein as an open term, specifying the presence of what follows the term in the text, but not excluding the presence of other components or characteristics, such as elements, steps, ingredients, known in the art or disclosed herein.
[0017] The expression "polymer" is used herein according to the definition given in the document entitled "How to determine whether a substance is a polymer and how to register it" (December 2017 edition) published by the European Chemicals Agency (ECHA). Therefore, in the present invention, the inventors define any chemical substance containing more than 50% by weight of "polymer molecules" as a "polymer"; wherein the "polymer molecule" is defined as a molecule comprising at least three basic units (monomers or more complex units) combined with a fourth unit, which may be the same as or different from the first unit. Therefore, the polymer molecule contains at least four basic units in total, which may be monomer units or more complex units (for example, when the basic units are composed of two or more monomers, as in the case of condensation polymers). The expression "one or more polymers" includes both polymer molecules formed by only one type of basic unit / monomer (homopolymers) and polymer molecules formed by multiple different types (copolymers).
[0018] In a similar manner, the expression "oligomer" herein refers to a chemical substance comprising more than 50% by weight of "oligomer molecules"; wherein said "oligomer molecules" comprise less than three basic units (monomers or more complex units) bonded to another unit, which may be the same or different from the first unit. In addition, the expression "one or more oligomers" includes both oligomer molecules formed from only one type of basic unit / monomer (homo-oligomers) and oligomer molecules formed from a plurality of different types (co-oligomers).
[0019] More specifically, the expression "homopolymer" is used herein according to the definition given in the article "Compilation of Basic Terms in Polymer Science" published by IUPAC (International Union of Pure and Applied Chemistry) in "Pure and Applied Sciences" Volume 68, Issue 12, Pages 2287-231, 1996. Therefore, the expression "homopolymer" refers to a polymer synthesized from only one monomer in this article. Still according to the same reference, the expression "copolymer" in the present invention (unless a different meaning is specifically indicated) refers not only to a polymer using two different monomers in a chemical composition, but also to a polymer using three, four, five or more different monomers in a chemical composition. According to the above reference, when it is necessary to emphasize the number of different comonomers forming a certain copolymer, the expressions "binary polymer", "ternary polymer", "quaternary polymer" and the like can also be used as an alternative.
[0020] "Polydispersity index", "molecular weight distribution index" or "PDI" refers to a measure of the molecular weight distribution in a certain polymer. It is defined as the ratio between the weight average molecular weight Mw and the number average molecular weight Mn: PDI = Mw / Mn. The larger the PDI value, the broader the molecular weight distribution curve, and vice versa. Mw, Mn and their ratio Mw / Mn = PDI can be measured, for example, by gel permeation chromatography (GPC).
[0021] The expression "bimodal composition" when referring to a polymer composition means that the composition is formed by two polymers which are compatible with each other and are intimately dispersed in each other on a submicroscopic scale; the polymers differ in their average molecular weight and / or in their chemical composition and / or in these two properties. The polymer compositions with a bimodal composition can be obtained in two separate and distinct synthesis steps within the production reactor itself during the polymerization step; or, on the contrary, they can also be produced by mechanical blending on a submicroscopic scale of two polymers which have been synthesized separately and subsequently intimately blended in the molten or solution state.
[0022] The melting enthalpy, crystallization enthalpy and glass transition temperature of a material are measured here by differential scanning calorimetry (DSC) according to standard methods ASTM D3417-99 and ASTM D3418-12. For measuring all these parameters, a temperature ramp rate equal to 10°C / min is always used here.
[0023] For a certain material, when a DSC melting or crystallization diagram shows two or more peaks (even if partially overlapping), it is defined herein as the "peak melting temperature" of the material or the "peak crystallization temperature" of the material, that is, the peak temperature of the peak with the largest area and therefore the largest enthalpy.
[0024] "Room temperature", if not specifically defined differently, means a temperature equal to 23°C; and "room conditions" means environmental conditions at controlled temperature and relative humidity, at 23°C and 50% relative humidity.
[0025] Since the properties of some materials (for example the amount and morphology of their crystalline fractions, and therefore their enthalpy of melting and their mechanical properties) vary as a function of the time elapsed from the molten state to the moment of their solidification, a distinction is made in the present invention between "properties at time zero" and "aged properties" after a certain number of aging hours or days (usually five days) after the material has solidified from the molten state.
[0026] Therefore, a property "at time zero" (for example, the enthalpy of melting at time zero), also referred to as an "initial" property or a property "under initial conditions", means that the property is measured at 23°C (unless a different temperature is specifically noted) and 50% relative humidity within a period of no more than 120 minutes after the material being tested solidifies from a molten state.
[0027] In contrast, a property such as "five-day aging" or "five days" or "under aging" means that the property is measured at 23°C (unless a different temperature is specified) and 50% relative humidity five days after the material being tested has solidified from the molten state. During the five-day aging process, the material being tested is stored in a climate-friendly room at 23°C and 50% relative humidity.
[0028] The expression "non-solid" is used herein to mean that certain compounds or materials or components or blends thereof are in a physical state in which, even though they have a well-defined volume, they do not have a fixed shape of their own, but rather take on the shape of the container in which they are contained. Even in the case where they are viscous enough to temporarily form themselves into any three-dimensional shape, upon standing still and without any external stress other than their own weight, they spontaneously flow and permanently deform, thereby quickly (usually within a few seconds to about a day) losing their initial shape, taking on the shape of the container in which they are contained (if these containers are not already filled to the brim) or the shape of the solid surface on which they are spread. Thus, this definition includes not only all materials that can be defined as "liquids" (high and low viscosity) according to the common meaning of this adjective, but also all materials that are defined in common language, for example, as "creamy", "paste-like", "jelly-like", "fluid", "greasy", "semi-solid", etc. Another way to define in rheological terms what is meant when a certain compound or material or component or blend thereof in the present invention is referred to as a "non-solid" at room temperature (i.e., typically at a temperature of 23°C) is that the substance that specifies the "non-solid" can be defined as a "rheological liquid", that is, as defined in rheology, the viscous modulus G" of the substance at a specified temperature of 23°C is higher than its elastic modulus G', or equivalently, by definition, the Tan Delta of the substance is greater than 1.
[0029] The equivalent expression "rheological solidification point" or "rheological solidification temperature" or "temperature of rheological solidification", or "modulus crossover temperature" or "crossover point" and its symbol Tx refers to the temperature at which the elastic modulus G', the viscous modulus G and their ratio Tan Delta are measured as a function of temperature in the rheological diagram, where the two moduli cross in the temperature region above room temperature (so the value of Tan Delta is equal to 1). It indicates the temperature at which the material being tested solidifies or melts in the rheological sense (changes from the molten state to the solid state or vice versa).
[0030] “Absorbent hygiene products” refers to devices and / or methods related to disposable absorbent and non-absorbent products, including diapers and undergarments for incontinent adults, infant diapers and bibs, training pants, infant care wipes, feminine catamenial pads, interlabial pads, panty liners, pessaries, sanitary napkins, tampons and tampon applicators, wound dressing products, absorbent nursing pads, cleansing wipes, etc.
[0031] "Perforated film" refers to a film usually made of plastic materials such as polyethylene, which is perforated with multiple holes and can have two-dimensional and three-dimensional structures. The typical hole size ranges from a few hundred microns to about one millimeter. It is usually used as a component of absorbent hygiene products.
[0032] "Fiber substrate" refers to a product having a substantially planar structure, formed from natural or synthetic fibers or blends thereof, including woven and nonwoven fabric forms, as such are used as a component of absorbent hygiene products.
[0033] The "open time" of an adhesive refers to, particularly for a hot melt adhesive, the time interval after it is applied from the melt to the first substrate, during which the adhesive is able to form a sufficiently strong bond with a second substrate in contact with the first substrate under moderate pressure for the intended use. Obviously, too short an open time may make it difficult to manage the application of the adhesive and the formation of a sufficiently strong bond. The open time of a hot melt adhesive can be measured according to test method ASTM D 4497-94, and the conditions for the hot melt adhesive disclosed herein are as follows:
[0034] - Adhesive film coating temperature: 170°C
[0035] -Thickness of adhesive film: 1 mm.
[0036] "Ring & Ball softening point" refers to the softening temperature of a material, measured according to method ASTM D 36-95.
[0037] For waxes only, the "softening point" (also called the "dropping point") is measured according to method ASTM D 3954-94.
[0038] The "needle penetration" of an adhesive is a measure of its softness. It is usually expressed as tenths of a millimeter (dmm) and is measured herein according to method ASTM D1321-04 at 55°C.
[0039] The dynamic viscosity of a molten or liquid material at a certain temperature is expressed in mPa·s and is measured according to method ASTM D3236-88.
[0040] The melt flow rate (MFR) of the polymeric material is expressed in g / 10 minutes and is measured according to method ISO 1133-1 at 190°C and 2.16 kg weight.
[0041] The tack of an adhesive is measured herein according to method ASTM D6195-03.
[0042] The total bond strength or "peel strength" is defined as the average strength per unit width required to separate two substrates bonded by the tested adhesive, determined by a separation test carried out at a controlled and constant speed and at a controlled and fixed debonding angle. The measurement is carried out herein according to the method ASTM D 1876-01, separating the two substrates at a debonding angle of 180 degrees by applying a separation speed of the two substrates equal to 150 mm / minute, which means that the test dynamometer actually moves at a speed of 300 mm / minute. The two substrates used herein are supplied by Poligof (Italy) with a basis weight of 23 g / m 2 A polyethylene film on which a 1.5 g / m 2 The molten adhesive at 165°C was directly applied and immediately bonded thereto with a basis weight of 12 g / m supplied by Union Industries (Italy). 2 Spunbond polypropylene nonwoven fabric. The laminated structure formed by the glued plastic film and the nonwoven fabric was then aged and conditioned for five days at 23°C and 50% relative humidity. After this aging, the peel strength was tested according to method ASTMD 1876-01 by cutting the necessary samples from the bonded laminate (six samples were tested for each measurement). In each test, the peel strength was measured by recording the average strength (in Newtons (N)) required to separate the two bonded substrates over a width of 50 mm; after six tests for each adhesive, the peel strength was calculated as the average of the strengths recorded in the six tests.
[0043] The "tensile properties" or "tensile mechanical properties" of all materials (such as hot melt formulations) disclosed herein, such as the so-called "stress-strain curve", and the respective "peak stress" or "ultimate tensile strength"; "breaking stress"; and "breaking elongation", etc., are measured according to the following method at 23°C and 50% relative humidity (unless otherwise specified). For each material tested, a film with a thickness of 0.5 mm was extruded at 170°C. Five rectangular samples with a length of 25 mm and a width of 6 mm were cut from the extruded film. If required by the type of test, the samples were aged for five days at 23°C and 50% relative humidity. To evaluate its breaking stress-strain curve, each sample was fixed at its narrowest end with a clamp on the axis of a rheometer Ares G2 available from TA Instruments, which is equipped with the so-called "Torsion Rectangular" geometry for tensile testing. The free length of the sample is 10 mm. The maximum extension distance of the movable upper axis is 60 mm (therefore corresponding to a maximum readable strain of 600%), starting with an extension rate equal to 6 mm / minute. Therefore, these test conditions correspond to a sample strain rate equal to 0.1s -1 , i.e. the frequency is 0.1 Hz. The tensile test is stopped when the sample breaks or when the rheometer reaches the maximum readable strain (equal to 600%). For each fracture stress-strain curve, the rheometer measures the maximum "peak stress" or "ultimate tensile strength", the maximum strain, and also calculates the area under the curve itself, which is equal to the area of the material toughness, expressed as J / m 3 .
[0044] The rheological properties of materials (e.g., polymers or adhesive formulations) are measured herein using a rheometer Ares G2 available from TA Instruments. For rheological properties measured "at time zero" when the temperature is reduced, the sample is melted between the plates of the rheometer by raising the temperature to 150°C and conditioning the molten material at this temperature for 600 seconds. Thereafter, the temperature is reduced at a rate of 2°C / min at a strain frequency of 1 Hz, and the rheological test is started until the sample reaches a temperature of -20°C, at which the test is stopped.
[0045] For rheological properties measured under conditions of increasing temperature (or vice versa), the following test conditions are used. If the property in question is "at time zero", the test follows the same procedure as described in the previous paragraph for the test at decreasing temperature. However, when the sample reaches a temperature of -20°C, it is conditioned at this temperature for 600 seconds; the test is then restarted by increasing the temperature at a rate of 2°C per minute at a frequency of 1 Hz until a final temperature of 150°C is reached.
[0046] However, when it is desired to measure the rheological properties aged for five days at elevated temperatures, the following procedure is used: the sample is melted at 150°C between the plates of the rheometer and conditioned at this temperature for 600 seconds. Then, without any measurements, the sample is cooled to a temperature of 23°C while still between the plates of the rheometer. The entire system is left at a temperature of 23°C and a relative humidity of 50% for five days. When the five-day aging time has elapsed, the sample is further cooled to -20°C and conditioned at this temperature for 600 seconds. Thereafter, the measurement is started by increasing the temperature at a rate of 2°C / min at a frequency of 1 Hz until a final temperature of 150°C is reached, after which the test is stopped.
[0047] Other less common parameters measured according to specific methods are defined below and their measurement methods are described in detail. Background Art
[0048] From a historical perspective, isotactic butene-1 homopolymers and copolymers have been manufactured and sold industrially since 1964 by companies such as Huls, Mobil, Witco, but primarily by Shell, which has been the major global supplier since 1977. The production of these polymers and polymer grades has subsequently been transferred to LyondellBasell.
[0049] All "old generation" isotactic polybutene-1 and its copolymers are manufactured by using Ziegler-Natta catalysts, which produce polymers with extremely high polydispersity indexes, usually greater than 4 and often even greater than 6. Therefore, these polybutene-1 show a very wide molecular weight distribution in the same polymer, most of which is formed by very high and very low molecular weights. In fact, in the Ziegler-Natta process, in order to obtain a sufficiently high final average molecular weight to give the polymer acceptable mechanical properties, it is therefore necessary (if, for example, Mw / Mn is equal to or greater than 4) to synthesize a large part of the polymer chains with very high molecular weights. Therefore, these "old generation" isotactic polybutene-1 also show high or very high viscosity in the molten state.
[0050] Furthermore, since its discovery in 1954 by the Nobel Prize winner Giulio Natta, it has been recognized that isotactic polybutene-1 and its copolymers show a very specific behavior with regard to crystallization after solidification from the molten state. In fact, while all other major polyolefins capable of crystallization, such as polyethylene or polypropylene, reach their final crystal structure and percentage of crystallinity in a very fast manner, often in an almost instantaneous manner, isotactic polybutene-1 crystallizes in a very different manner, which is usually defined as a long “delayed crystallization”. This delayed crystallization in time is a very complex phenomenon, taking into account the crystalline polymorphism of isotactic polybutene-1; due to this phenomenon, after solidification of the polymer from the molten state, not only does its crystallinity level grow slowly over time, but it also slowly transforms from an initial metastable crystalline form, called Form II, to a stable crystalline form, also called Form I. This phenomenon leads to a quantitative and qualitative evolution of the crystallinity of solid isotactic polybutene-1 over time, also at room temperature, and is usually completed within a period of three to seven days, with an average of five days. This special behavior in the crystallization of isotactic polybutene-1 is described, for example, in the article published by Choi et al., "Timedependent crystallinity of polybutene-1", Polymer Engineering and Science, Vol. 6, No. 4, October 1966, pp. 349-352; and the article published by Xin et al., "Polymorphic Behavior and Phase Transition of Poly (1-Butene) and its Copolymers", Polymers, 10 (5): 556, May 2018.
[0051] The high molecular weight and high melt viscosity properties of the "old generation" isotactic polybutene-1 with a polydispersity index greater than 4 mentioned above have often forced attempts to use these polymers as base polymers for hot melt adhesives (starting with Shell itself) to formulate adhesives containing relatively low amounts of polybutene-1 (for ease of processing); therefore, they contain significantly higher percentages of other typical components of hot melt adhesives, i.e., components with low or very low molecular weight, e.g., Mn typically well below 2500 g / mol, such as tackifiers, viscosity modifiers and waxes.
[0052] For example, in Shell patent US4937138, the inventors claim hot melt adhesives containing 5% to 50% of a butene-1 based polymer formulated with up to 50% to 95% of a tackifier and optionally up to 60 parts of low molecular weight additional ingredients such as viscosity modifiers or waxes per 100 parts of the blended polymer plus tackifier. Unfortunately, the patent does not disclose the viscosity of the formulations of the examples of the present invention. However, another quite similar patent US4568713 of Shell shows in Table II that hot melt adhesives containing 50% by weight of butene-1 homopolymer or copolymers of butene-1 with different levels of ethylene have extremely high viscosities of 20,000 to 25,000 mPa·s at temperatures up to 177°C, while processability is very difficult and unsatisfactory.
[0053] Likewise, US5256717 shows three formulations in Table 1 which contain as little as 20 wt% of Duraflex 8910, a Ziegler-Natta copolymer of butene-1 and ethylene, blended with up to 80 wt% of tackifiers and viscosity modifiers in order to have reasonable viscosity at temperatures up to 177°C (350F).
[0054] Furthermore, for example, US5786418 claims in claim 1 a polybutene-1 content of 10 to 60 wt %, but actually states in column 2, lines 23 to 34 that the scope of the invention is to disclose a preferred adhesive formulation containing only 25 wt % of a polymer which is a copolymer of butene-1 and ethylene, and up to 75 wt % of low molecular weight components, such as tackifiers and viscosity modifiers.
[0055] Even though the prior art has shown examples of hot melt adhesives containing relatively high amounts (e.g. 50% by weight or more) of these butene-1 polymers, which are synthesized with Ziegler-Natta catalysts and therefore have a polydispersity index greater than 4 and have a large proportion of high molecular weight or ultra-high molecular weight, it has been shown that the preparations generally exhibit such high viscosities in the molten state that their processability is extremely poor and difficult, especially on industrial production lines running at high speeds, such as 200 m / min or even higher. In addition to the already mentioned US456871, EP0314495A2 may also be considered, which shows in its Tables 1 and 2 seven embodiments and four comparative examples according to the invention. All of these embodiments contain 50% by weight of various homopolymers or copolymers of butene-1, which are synthesized with Ziegler-Natta catalysts, the remaining 50% by weight in the preparation being tackifiers. EP0314495A2 does not disclose the viscosities of these adhesives shown in the examples. However, the inventors of the present invention experimentally measured the melt viscosity of Example 2 in Table 2 of EP0314495A2 according to the present invention and found values as high as 50200 mPa·s at 170° C. and 36300 mPa·s at 177° C. These viscosities are so high for hot melt adhesives that it is practically impossible to process these hot melt formulations on high-speed industrial production lines (e.g., 200 m / min or more), nor on production lines running at much lower speeds; in any case, these very viscous adhesives are extremely difficult to process even on production lines operating at unacceptably low speeds (e.g., 5 m / min).
[0056] The need to formulate these older generation polybutene-1s synthesized with Ziegler-Natta catalysts with extremely high polydispersity indexes (generally greater than 4) leads to various problems, if in order to obtain adhesive formulations with sufficiently low viscosity, one has to formulate adhesives with particularly low polymer content, so that the content of low molecular weight components is much higher and dominant, such as the usual tackifiers, viscosity modifiers and waxes. In fact, the low molecular weight components tend to delaminate over time and migrate out of the formulation containing a high percentage of the light components, eventually seeping out from the adhesive surface. These phenomena have very negative consequences, first of all, this leads to unacceptable changes and degradation of the properties of the adhesive itself over time. In addition, this molecular migration and the seepage of low molecular weight components on the adhesive surface can lead to the generation of bad odors, and if these exudates come into contact with the user's skin, they can cause severe skin irritation, sensitization, allergies and even toxic reactions.
[0057] In addition to these highly negative and unacceptable phenomena, when the adhesives are used for medical articles and absorbent hygiene articles, too low a polymer fraction content also has a strong negative impact on the special "delayed crystallization over time" exhibited by polybutene-1 and its copolymers when we consider hot melt adhesives based on butene-1 polymers. In fact, an excessive "dilution" of the fraction formed by butene-1 polymers with a high polydispersity index may lead to further negative effects that affect the crystallization of said polymers. For example:
[0058] - the dilution of the polymer chains may itself lead not only to a slowing down of their crystallization, but may even lead to a deterioration in the "quality" of the crystallinity formed itself, since, with the same final crystallinity, in a more dilute environment it is statistically more likely that more crystals will form, which are however smaller and "weaker" and more dispersed in the mass of the adhesive;
[0059] - One could reasonably assume that the exclusive use of butene-1 polymers with a high polydispersity index might increasingly lead to the formation of many crystals in an almost uncontrolled manner, which are however, on average, smaller, weaker and less "perfect", due to the presence of a large number of polymer chains of very low molecular weight, each of which could serve as a nucleating agent / crystallization initiator.
[0060] - The presence of a significant fraction of high and ultra-high molecular weight, even in a hot melt adhesive containing only butene-1 polymers with a high polydispersity index, can have a significant negative impact on the quality and quantity of the final crystalline phase that can be obtained. In fact, as is well known in polymer science, the level of final crystallinity that can be obtained during the crystallization of a polymer and the "quality / perfection" of the crystals are inversely proportional to the average molecular weight of the polymer itself; these characteristics decrease / deteriorate with increasing average molecular weight of the same polymer, as is clearly shown for example in the book "Crystallization of Polymers" edited by Marcele Dosiere, pages 26 et seq.
[0061] However, it should be noted that, in hot melt adhesives containing only polybutene-1 with a high polydispersity index, the presence of significant very low and very high molecular weight fractions also has some positive effects on some important properties of the hot melt adhesive. In fact, as is well known to the average technician in each hot melt adhesive science field, if the average molecular weight of the contained polymer remains constant, the presence of a large number of low molecular weight or very low molecular weight polymer chains will cause the adhesive to show greater adhesion; in particular, they show higher viscosity and higher peel strength. On the contrary, the part with high molecular weight or very high molecular weight helps to improve (of course, in the case of the same polymer content in the adhesive and the equal average molecular weight of the polymer) the cohesion of the adhesive itself.
[0062] It is therefore concluded that the prior art does not teach how to formulate a hot melt adhesive based on "old generation" Ziegler-Nattabutene-1 polymers which exhibits low melt viscosity and excellent ease of processing on industrial production lines running at high speeds (e.g. above 200 m / min) while also combining the need to keep relatively low levels of other low molecular weight non-polymeric ingredients / additives such as tackifiers, viscosity modifiers and waxes. As mentioned above, this latest need aims to avoid the migration and exudation of these light additives, which phenomena may lead to further very negative effects, such as unacceptable changes in the main adhesive properties over time, the generation of bad odors, possible allergic reactions and even toxic effects if these exuded light ingredients come into contact with the user's skin. However, all this is of course without giving up the beneficial effects of those very low and very high molecular weight polymer parts on other essential properties of the adhesive, especially on good tack and peel strength and sufficient cohesion. Summary of the invention
[0063] The problem that the present invention aims to solve is to formulate a hot melt adhesive which has a relatively low viscosity in the molten state, so that it can be easily processed even on industrial production lines running at high speeds (e.g. above 200 m / min); and which exhibits an optimal balance between the main and critical properties of hot melt adhesives, in particular:
[0064] - high adhesion, especially manifested in high peel strength;
[0065] - The content of low molecular weight components (such as tackifiers, viscosity modifiers and waxes) is relatively low, the main goal is to minimize problems such as bad odor, allergic or toxic effects on users, because if these contents are too high, the light components will undergo molecular migration and bleed out of the adhesive;
[0066] - Qualitative and quantitative optimization of the typical time-delayed crystallization of butene-1 polymers with the aim of obtaining crystals that are as "robust" and morphologically "perfect" as possible, thus providing strong cohesion and mechanical properties even in the absence of excessively high molecular weights, which in turn would increase the melt viscosity of the adhesive too much.
[0067] This problem is solved by a hot-melt adhesive having the features of claim 1, an adhesively bonded structure having the features of claims 36 and 37, and an article having the features of claims 38 to 44. The further subclaims disclose preferred embodiments. DETAILED DESCRIPTION
[0068] The hot melt adhesive disclosed in the present invention comprises a polymer blend of two different types of polymers both based on butene-1 as its main component. In particular, the hot melt adhesive of the present invention comprises a polymer blend formed by blending at least two butene-1 polymers A) and B) in a balanced and appropriate ratio, wherein the polymers are characterized by the following properties:
[0069] A) The polymer A) is present in the blend at a level of 5 wt% to 95 wt%. It is a non-isotactic copolymer of butene-1, having a unimodal composition, a polydispersity index Mw / Mn of not less than 3.5, and is composed of butene-1 and one or more α-olefins selected from ethylene, propylene and C5 to C12 α-olefins. The polymer A) has a comonomer content of not less than 20 mol%, and also has the following thermal properties measured after aging for five days under room conditions:
[0070] - a melting enthalpy of not more than 40 J / g, preferably not more than 35 J / g and more preferably not more than 30 J / g;
[0071] - Peak melting temperature is not higher than 80°C;
[0072] - a glass transition temperature Tg measured by DSC of less than -10°C;
[0073] B) The polymer B) is present in the blend at a level of 95% to 5% by weight. It is an isotactic polymer composition of butene-1 having a bimodal composition and a global polydispersity index Mw / Mn of less than 3.5. It is in turn formed from two polymers B1) and B2) of butene-1. Specifically, the polymer composition comprises:
[0074] B1) 10 to 90% by weight of a butene-1 copolymer having one or more comonomers selected from ethylene, propylene and α-olefins having a carbon number equal to or greater than 5, the copolymer B1) having a copolymerized comonomer content of less than 20 mol % and a polydispersity index Mw / Mn of less than 3.5;
[0075] B2) 90 wt % to 10 wt % of a homopolymer of butene-1 or a copolymer of butene-1, which has one or more comonomers selected from ethylene, propylene and α-olefins having a carbon number equal to or greater than 5, the content of copolymerized comonomers of the homopolymer or copolymer B2) being not more than 5 mol % and having a polydispersity index Mw / Mn of less than 3.5.
[0076] The isotactic butene-1 polymer composition has the following thermal properties measured after five days of aging under room conditions:
[0077] - a melting enthalpy greater than 20 J / g, preferably greater than 25 J / g and more preferably greater than 30 J / g;
[0078] - Peak melting temperature above 90°C;
[0079] - The glass transition temperature Tg measured by DSC is not higher than -20°C.
[0080] The viscosity of polymer A) at 190° C. is between 1000 and 200,000 mPa·s, and the viscosity of polymer B) at 190° C. is between 1000 and 300,000 mPa·s. Furthermore, the weight ratio between components B1) and B2) of the isotactic butene-1 polymer composition B) is such that the total content of comonomer(s) thereof is less than 20 mol %, and preferably between 3 and 18 mol %.
[0081] In a preferred embodiment, the polymer blend comprising butene-1 polymer A) and B) has a weight ratio of A) to B) of greater than 1.
[0082] In another embodiment, the polymer blend comprising butene-1 polymers A) and B) further comprises 0 wt% to 30 wt% of a third butene-1 polymer C1). The butene-1 polymer C1) may be a homopolymer or a copolymer; in this latest case, butene-1 is copolymerized with one or more α-olefins selected from ethylene, propylene and C5 to C12 α-olefins. The polymer C1) is also characterized by a content of copolymerized comonomer (or multiple comonomers) of less than 20 mol%, a polydispersity index of greater than 3.5, a melting enthalpy after aging for five days of greater than 20 J / g; a peak melting temperature (still at five days) of greater than 80°C, and a glass transition temperature measured by DSC after aging for five days of no greater than -10°C.
[0083] In a third embodiment, as an alternative to the previous embodiments, the polymer blend comprising butene-1 polymers A) and B) also comprises from 0% to 30% by weight of another butene-1 polymer C2). The butene-1 polymer C2) may be a homopolymer or a copolymer; in this latest case butene-1 is copolymerized with one or more α-olefins selected from ethylene, propylene and C5 to C12 α-olefins. In addition, the polymer C2) is also characterized by a content of copolymerized comonomer (or multiple comonomers) of not less than 20 mol%, a polydispersity index of less than 3.5, a melting enthalpy after aging for five days of not more than 40 J / g; a peak melting temperature (again at five days) of not more than 90°C and a glass transition temperature measured by DSC after aging for five days of not more than -20°C.
[0084] In a fourth embodiment, the butene-1 polymers C1) and C2) have a unimodal composition.
[0085] In a fifth embodiment, the total polymer blend contained in the hot melt adhesive according to the present invention further comprises 0 wt % to 30 wt % of a polymer (i.e. a homopolymer or a copolymer) that does not contain butene-1. Preferably, the polymer that does not contain butene-1 is a polyolefin, and even more preferably, the polyolefin is a homopolymer or a copolymer synthesized from one or more alpha-olefins selected from ethylene, propylene and C5 to C12 alpha-olefins.
[0086] In a sixth embodiment, the polyolefin includes hexene.
[0087] In a seventh embodiment, said polymer in which butene-1 is absent from its composition is a copolymer of propylene and ethylene.
[0088] In an eighth embodiment, said copolymer between propylene and ethylene has a heterophasic structure.
[0089] Typically, the sum of all polymers present in the hot-melt adhesive according to the invention constitutes from 5% to 99.5% by weight, or from 60% to 99.9% by weight, of the adhesive itself.
[0090] More detailed information on the essential polymer constituents of the hot-melt adhesives according to the invention and on further possible additional components is given below.
[0091] Isotactic butene-1 polymer compositions having low polydispersity index, low viscosity and bimodal composition
[0092] Isotactic polymers based on butene-1, with high polydispersity index, synthesized with Ziegler-Natta catalysts, with high molecular weight and high viscosity in the molten state, have for many years dominated the market for polybutene-1 and its copolymers, not only for the adhesive sector. However, recently some companies producing isotactic polybutene-1 have abandoned the classical Ziegler-Natta catalysts and switched to new metallocene catalysts. These new processes allow the synthesis of a "new generation" of polybutene-1, which exhibits new and substantially improved properties, such as significantly smaller and better controlled average molecular weight (and therefore much lower melt viscosity), much smaller polydispersity index Mw / Mn, all of which lead to improved properties of these polymers, such as excellent cohesion and strong mechanical properties even at relatively low melt viscosities.
[0093] In particular, the company LyondellBasell has started to produce isotactic butene-1 polymers synthesized with metallocene catalysts, which polymers show a very special composition and structure, as well as new and significantly improved properties compared to all previous "old generation" isotactic butene-1 polymers. These new metallocene butene-1 polymers are sold under the trademark Koattro PB M. In particular, these new isotactic butene-1 metallocene polymers, such as described in patent applications EP3266824A1 and EP3266825A1, are polymer compositions formed from two different isotactic polybutenes. They therefore have a bimodal composition, in the sense that the average molecular weights of the two constituent polymers may differ, or their chemical composition may differ, or both of these properties may differ. The special bimodal compositions of polymers based on butene-1 can be obtained directly in two different and successive polymerization stages in the same reactor; or alternatively they can also be obtained by mixing two polymers at a submicroscopic level, which are synthesized separately and later intimately blended in the molten state or as a solution.
[0094] The overall mean number average molecular weight of the metallocene bimodal isotactic polybutene-1 polymer composition is generally not greater than 150,000 g / mol, preferably not greater than 100,000 g / mol and more preferably not greater than 80,000 g / mol.
[0095] These novel metallocene bimodal polymer compositions of isotactic polybutene-1 also have a high melt flow rate (and therefore a low melt viscosity) and a low total polydispersity index (less than 3.5, typically even less than 2.5). They are typically formed from a first polymer B1) which is an isotactic copolymer of butene-1 with one or more comonomers (selected from ethylene, propylene and α-olefins having a carbon number equal to or greater than five) and a relatively low comonomer content of not more than 20 mol %; and a second polymer B2) which is an isotactic homopolymer of butene-1 or an isotactic copolymer of butene-1 with one or more comonomers (selected from ethylene, propylene and α-olefins having a carbon number equal to or greater than five) and a lower comonomer content of 0 to 5 mol %. The two polymers of butene-1 are present in the polymer composition in a mutual ratio such that the total comonomer content in the composition is not more than 20 mol %, preferably from 3 to 18 mol %.
[0096] This high content of butene-1 (mainly in its isotactic form), as well as the particularly low polydispersity index values and the resulting absence of fractions with very low and very high molecular weights, leads not only to a significantly lower melt viscosity on average and thus to better processability (of course at the same average molecular weight of the polymers and the same content of the same polymer in the adhesive formulation), but also to various other positive effects on the "delayed crystallization" of the polybutene-1 in these special novel polymer compositions.
[0097] First, compared to the previous isotactic polybutene, the melt flow rate is higher, with MFR typically ranging from 40 g / 10 min to 6000 g / 10 min, corresponding to a melt viscosity range of about 1 Pa·s to 250 Pa·s at 190°C, allowing the formulation of adhesives that are more "concentrated" in the polymer, even on high-speed industrial production lines while still maintaining a relatively low viscosity, thus having excellent processability. This higher concentration of isotactic polybutene itself can obtain stronger and more "perfect" crystals on average.
[0098] Furthermore, the extremely low polydispersity index of these bimodal metallocene compositions of isotactic polybutene and the resulting absence of very low and very high molecular weight fractions further have a positive influence on the optimization of the qualitative and quantitative development of the delayed crystallization of molecules and molecular segments of isotactic polybutene over time.
[0099] Firstly, a low polydispersity index and therefore a narrow molecular weight distribution means that the molecular weights of all the molecules of a certain polymer are "more similar" therein than in other polymers having a larger polydispersity index; it is well known to all those skilled in the art of polymer science that the crystallization of a certain polymer matrix occurs in an easier way, i.e. the greater the number of crystals formed and the more "perfect" their quality, the more similar the molecular characteristics of the various chains of the polymer are in terms of their structure, composition, molecular weight (better if it is not too high), etc.
[0100] In addition to this, as described in the previous section, the absence of very low and very high molecular weight fractions in these novel metallocene, bimodal isotactic polymer compositions of butene-1 has, in itself, a qualitative and quantitative positive effect on the optimal development over time of delayed crystallization of isotactic polybutene-1. Indeed, for example, the substantial absence of very low molecular weight chains (each of which could serve as a nucleating agent and crystallization trigger) in these particular novel polymers eliminates the possibility that crystallization could start in a too rapid or uncontrolled manner, as well as the possibility that it could form an excessive amount of crystals (which are on average smaller and less strong, given the same overall level of crystallizable molecules and ultimately achievable level of crystallization). Or, in other words, the substantial absence of fractions of very low molecular weight isotactic polybutene-1 capable of crystallization in these polymer compositions, and therefore the absence of a very high number of possible crystallization nuclei / centers, allows (as is obvious to everyone skilled in the art of polymer science) the formation of crystals that are on average larger, stronger and more "perfect" in morphology in the hot melt adhesives according to the invention comprising these isotactic polybutene-1 polymer compositions than would be possible in similar adhesive formulations based on older generation isotactic polybutene-1, synthesized with Ziegler-Natta catalysts. This also effects a substantial improvement in the final properties of the hot melt adhesive formulations disclosed in the present invention, both in terms of adhesive properties and mechanical properties.
[0101] Thus, the presence of significantly fewer "spontaneous crystallization centers" (formed primarily by low and very low molecular weight isotactic polybutene-1 chains) results in the fact that in the hot melt adhesive formulations of the present invention, the isotactic polybutene-1 crystallizes more slowly, which has two major positive consequences. From one aspect, this slower and more controlled crystallization tends to extend the "open time" of the adhesives disclosed herein, having a favorable impact on the ease and effectiveness with which these adhesives can adhere to a variety of substrates. In addition, as already explained and well known to all those skilled in the art of polymer science, slower crystallization favors the formation of larger, stronger and more "perfect" morphological crystals, thus further improving the adhesion and mechanical strength / cohesion properties of the hot melt adhesive formulations disclosed herein.
[0102] Likewise, there is reason to believe that the virtually complete absence of high and very high molecular weight fractions in the adhesive formulations of the invention (which, in contrast, are present in large quantities in polybutene-1 from Ziegler-Natta catalysts) also has an important positive effect on the quality and quantity of the crystalline phases formed in the adhesives of the invention. For example, it is well known in polymer science that the ultimate "level of crystallinity" that can be achieved in a polymer and the "quality" of its crystals are inversely proportional to the average molecular weight of the polymer itself, as is clearly explained, for example, in the book "Crystallization of Polymers" edited by Marcele Dosiere, pages 26 et seq.
[0103] From all these considerations, it can be concluded that the hot melt adhesives comprising the above-mentioned isotactic butene-1 polymer compositions (having a bimodal composition and an overall polydispersity index of less than 3.5, preferably even less than 2.5) show, first of all, quantitatively and qualitatively, an optimal crystallization of chains and segments formed from isotactic polybutene-1 that is prolonged over time. In other words, in these isotactic polybutene-1 polymer compositions, a sufficiently slow crystallization occurs, which is usually completed in three to seven days, on average five days, under room conditions (i.e. 23° C. and 50% relative humidity). During this period, the number and size of the crystals increase, and the crystals also slowly transform from the initial metastable “Type II” (which is formed in a short time by solidification from the molten state) to the final stable form of isotactic polybutene-1, called “Type I”, which has better mechanical and thermal properties.
[0104] This is also indicated by the thermal properties of these isotactic polybutene-1 bimodal polymer compositions, which, after five days of aging under room conditions, have melting enthalpies generally greater than 20 J / g, peak melting temperatures greater than 90° C. and glass transition temperatures not greater than −20° C. These thermal properties, especially the first two, are clearly associated with the formation of particularly strong and “perfect” crystals, as measured by DSC.
[0105] All these phenomena are produced in the hot melt adhesive of the bimodal polymer composition comprising isotactic polybutene-1, which has very positive performance, particularly has excellent processability in spraying and slot die coating / extrusion, even on the industrial production line of high-speed operation equal to or greater than 200m / minute. This is due to low viscosity and narrow molecular weight distribution, i.e., there is no high molecular weight and very high molecular weight. In addition, also due to the particularly solid and morphological "perfect" structure formed in the slow crystallization process of isotactic polybutene-1 crystals delayed in time, excellent cohesion level is also achieved. Finally, due to the lower viscosity of these novel polymers, people can prepare these polymers with other low molecular weight components (such as tackifiers, viscosity modifiers or wax) at relatively low levels, so the hot melt adhesive of the present invention shows that there is no or significantly reduces the molecular migration and oozing of these low molecular weight components from the preparation, therefore, there is no or significantly reduces the negative important impact derived from the phenomenon, such as producing malodor and adhesive and user's skin contact when producing allergy or even toxicity.
[0106] Even considering hot melt adhesives comprising only the above-mentioned bimodal polymer compositions of isotactic butene-1, which have a low overall polydispersity index Mw / Mn, as their main polymer component, these hot melt adhesives undoubtedly already possess several very positive properties as described above.
[0107] However, especially for certain more demanding uses, these already positive properties of a hot melt of a bimodal polymer composition comprising only the above-mentioned isotactic butene-1 may not be sufficient.
[0108] For example, one of the most typical and important industrial uses in which hot-melt adhesives based solely on the above-mentioned bimodal polymer composition of isotactic butene-1 with a low Mw / Mn do not fully meet the most demanding requirements of the user is the use when the thermoplastic adhesive has to adhere to particularly "difficult" to bond substrates, such as substrates usually made of plastics with a low surface tension, in particular polyolefin films (whether perforated or not); or nonwovens still made of polyolefins, and such combinations of polyolefin films bonded / laminated to polyolefin nonwovens (for example in the manufacture of absorbent hygiene products such as baby diapers). In fact, in these uses, it may happen that the hot-melt adhesive comprising only the above-mentioned bimodal polymer composition of isotactic butene-1 (whose overall polydispersity index is low) as its main polymer component also shows some defects and performance deficiencies in relation to other properties (in addition to the undoubted positive properties already mentioned). This is true first of all in relation to the above-mentioned aspects related to the tack and insufficient adhesion (for example, expressed in terms of peel strength) on the "difficult to bond" polyolefin substrates. As mentioned above, the fact that low molecular weight and the absence of very low molecular weight may also have a negative impact on certain adhesive properties such as tack and peel strength, especially when it is necessary to achieve sufficiently strong adhesion on substrates with very low surface tension (and therefore difficult to be "wetted" and adhered to by hot-melt adhesives), such as plastic films and nonwovens made of polyolefins.
[0109] In order to resolve this apparent contradiction, in the context of the need to maintain at a maximum level the exceptionally excellent properties imparted to hot melt adhesives by the above-mentioned bimodal isotactic butene-1 polymer composition (having a low polydispersity index of less than 3.5) while not giving up the optimum values for tack and adhesion (which on the contrary usually result in the adhesive from the presence of some polymer chains of low and very low molecular weight (e.g. typically 300 to 5000 g / mol)), the inventors of the present invention surprisingly found that by blending said bimodal isotactic butene-1 polymer composition (Mw / Mn less than 3.5) with different copolymers also based on butene-1 in the hot melt adhesives disclosed herein, this unexpected combination of positive properties, namely good processability, low melt viscosity and excellent cohesion (all properties imparted by the bimodal isotactic butene-1 polymer composition with a Mw / Mn less than 3.5), yet combined with very good tack and adhesion, even on difficult-to-bond substrates such as polyolefin films and nonwovens, can be achieved in a completely unexpected manner. In contrast, these various copolymers of butene-1 are non-isotactic, have a unimodal composition and a polydispersity index Mw / Mn of not less than 3.5, generally not less than 4 and in some cases even not less than 6; i.e. these copolymers, which are still based on butene-1, nevertheless also contain not negligible low and very low molecular weight fractions, for example in the range of 300 to 5000 g / mol.
[0110] The non-isotactic and unimodal copolymers of butene-1 at high polydispersity index Mw / Mn not only impart excellent tack and adhesion to the hot melt adhesive formulations of the invention even on difficult-to-bond substrates, but also, surprisingly, improve the already good processability even on production lines running at high speeds, in particular for slot die extrusion and coating applications.
[0111] Thus, polymer blends between the above-mentioned bimodal polymer composition of isotactic butene-1, having a low polydispersity index Mw / Mn, typically less than 3.5 (generally referred to herein as "polymer B"), and the above-mentioned non-isotactic unimodal copolymer of butene-1, having a polydispersity index also not less than 3.5, typically not less than 4, and even not less than 6 (generally also referred to herein as "polymer A"), provide in a completely unexpected and surprising manner a combination of the most positive properties typical of two different types of polymers both derived from butene-1. At the same time, these blends also surprisingly offset or at any rate reduce the negative properties of the two types of butene-1 polymers, such as the high melt viscosity and poor cohesion typical of non-isotactic butene-1 polymers having a high Mw / Mn, having significant very high and very low molecular weight fractions, to a very small or even undetectable level.
[0112] The inventors have even more surprisingly found that in blends of said polymer A) with polymer B), even in hot melt adhesives in which the weight ratio between polymers A) and B) is greater than 1, the optimization of the positive properties of both butene-1 polymers can be achieved in an optimal manner while keeping their various negative characteristics at a negligible level, provided that said non-isotactic unimodal copolymer of butene-1 having a polydispersity index of not less than 3.5 further exhibits the properties described in more detail in the following paragraphs.
[0113] Heterotactic copolymers of butene-1 with high polydispersity index and unimodal composition
[0114] In order to be advantageously used in the above-mentioned polymer blends on which the hot-melt adhesives according to the invention are based, which blends may contain 5 to 95% by weight of polymer A) and 95 to 5% by weight of polymer B), these already partially described non-isotactic unimodal copolymers of butene-1 having an Mw / Mn value of not less than 3.5 must also be selected according to the further properties described below.
[0115] These copolymers, referred to herein as polymer A), are formed by copolymerizing butene-1 in non-isotactic form with one or more α-olefins selected from ethylene, propylene and C5 to C12. The synthesis can be carried out with any type of catalyst (for example a Ziegler-Natta catalyst), provided that the resulting copolymer does not contain a large amount of chains with an isotactic structure and that its final polydispersity index Mw / Mn is not less than 3.5, preferably even greater.
[0116] Their average molecular weight must be comprised within well-defined ranges that are not too high; more specifically, the number average molecular weight of these non-isotactic butene-1 copolymers is not greater than 30,000 g / mol, and preferably not greater than 20,000 g / mol. With these average molecular weights, their melt viscosity at 190° C. is generally between 1 Pa·s and 200 Pa·s, but is preferably much lower, for example between 1 Pa·s and 50 Pa·s.
[0117] Unlike polymer B), i.e. an isotactic butene-1 polymer composition having an overall Mw / Mn of less than 3.5 and having a bimodal composition, these butene-1 non-isotactic copolymers A) have a unimodal composition. Furthermore, while polymer B) contains in its chemical composition a predominant amount of butene-1 greater than 80 mol%, preferably from 82 mol% to 97 mol%, the butene-1 non-isotactic unimodal copolymers A) have a significantly higher level of comonomer (as said comonomer copolymerized with butene-1), never less than 20 mol%.
[0118] These non-isotactic unimodal copolymers of butene-1 have a high polydispersity index and are also characterized by the following thermal properties measured after five days of aging under room conditions:
[0119] - Melting enthalpy is not more than 40 J / g;
[0120] - Peak melting temperature is not higher than 80°C;
[0121] - The glass transition temperature Tg measured by DSC is below -10°C.
[0122] These thermal properties, especially the first two, imply not only the substantial absence of butene-1 segments capable of crystallizing in an isotactic structure in these copolymers, but also indicate a low overall degree of crystallinity, which in any case may be formed, which differs significantly in quantity and quality from the crystallinity formed within the other butene-1 polymers B).
[0123] Copolymers of butene-1 having a unimodal composition and a polydispersity index of not less than 3.5 can be used in the present invention as polymer A) blended with polymer B), such as those manufactured and sold under the trademark Vestoplast by Evonik and Rextac by Rextac.
[0124] As mentioned above, the polymer part of the hot melt adhesive disclosed in the present invention may contain 0 to 30 wt % of other polymers described above in addition to polymer A) and polymer B).
[0125] The sum of all polymers contained in the hot-melt adhesive according to the invention constitutes 5% to 99.5% by weight of the hot-melt adhesive itself.
[0126] In another embodiment, the sum of all polymers contained in the hot melt adhesive according to the invention constitutes 60% to 99.5% by weight of the hot melt adhesive.
[0127] Additional components
[0128] The hot melt adhesive of the present invention may also contain other additional components. In particular:
[0129] Tackifier
[0130] In an embodiment of the present invention, the adhesive formulation according to the present invention also contains 0% to 70% by weight of a tackifier resin or a blend of tackifier resins. The ring and ball softening point of the tackifier or tackifier blend is from 5°C to 160°C, and is preferably not less than 70°C. It can be selected from: aliphatic hydrocarbon resins and partially or fully hydrogenated derivatives thereof; aromatic hydrocarbon resins and partially or fully hydrogenated derivatives thereof; aliphatic-aromatic hydrocarbon resins and partially or fully hydrogenated derivatives thereof; polyterpene resins and modified polyterpene resins and partially or fully hydrogenated derivatives thereof; rosin, its esters and partially or fully hydrogenated derivatives thereof. Hydrogenated tackifier resins, whether aliphatic or aromatic or aliphatic-aromatic hydrogenated tackifier resins, are particularly preferred because they show optimal compatibility with butene-1 polymers (polymer A) and polymer B), both of which are the main components of the adhesive of the present invention as mentioned above).
[0131] Viscosity modifiers that are not solid at room temperature
[0132] In a second embodiment of the present invention, the hot melt adhesive disclosed herein further comprises 0 wt % to 40 wt % of at least one viscosity modifier or a blend of viscosity modifiers, which is not solid at room temperature (i.e., 23° C.). The viscosity modifier or blend of viscosity modifiers is selected from paraffinic mineral oils; naphthenic mineral oils; paraffinic hydrocarbons and cycloalkanes and their blends that are not solid at room temperature; oligomers and polymers of C2 to C20 polyolefins that are not solid at room temperature, and their co-oligomers and copolymers that are not solid at room temperature; other viscosity modifiers that are not solid at room temperature and are formed from ester chemistry, such as phthalates, benzoates, sebacates, citrates, tartrates; vegetable oils; synthetic fats and natural fats; and blends thereof.
[0133] In a preferred sub-embodiment, the oligomers and polymers of the above C2 to C20 polyolefins (not solid at room temperature) are synthesized with metallocene catalysts; or in any case have a polydispersity index of less than 3.5 and preferably less than 2.5. Viscosity modifiers of this type are manufactured and sold by companies such as ExxonMobil under the trademarks SpectraSyn and Elevast; Durasyn under the trademark Durasyn; Chevron Phillips under the trademark Synfluid; Clariant under the trademark Licocene PPA 330.
[0134] wax
[0135] In a third embodiment of the present invention, the hot melt adhesive disclosed herein comprises at least one wax or a blend of waxes in an amount of 0 to 10 wt %, preferably 0 to 5 wt %.
[0136] In another preferred sub-embodiment, the wax or wax blend is a polyolefin wax or a blend of polyolefin waxes, the one or more polyolefin waxes also containing more than 50 mol % of ethylene or propylene and having a viscosity at 190° C. of not more than 2000 mPa·s.
[0137] In additional embodiments, the ethylene or propylene based polyolefin wax or blend of polyolefin waxes is modified with maleic anhydride.
[0138] Other optional components
[0139] Furthermore, the hot melt adhesive according to the invention may contain 0.01% to 10% by weight of at least one stabilizer, such as antioxidants, light stabilizers, UV stabilizers and blends thereof.
[0140] They may further contain up to 15% by weight of other optional additional components such as mineral fillers, pigments, dyes, fragrances, surfactants, antistatic agents.
[0141] Example
[0142] The following examples better illustrate the present invention, which are given for illustrative purposes only and should not be considered to limit the scope or practice of the present invention. Unless otherwise specifically stated, parts and percentages are given by weight.
[0143] According to the embodiment of the present invention
[0144] Example 1
[0145] According to the invention, the following hot melt adhesive formulation was prepared by mixing its ingredients in the molten state at 170° C.:
[0146]
[0147] The hot melt adhesive formulation of Example 1 contains a blend of two butene-1 polymers, Rextac RT 2830 and Koattro PBM 1500M, as its polymer matrix.
[0148] Rextac 2830 available from Rextac (USA) is a non-isotactic butene-1 copolymer synthesized using a Ziegler-Natta catalyst and is believed to consist of about 55 mol% butene-1 and 45 mol% propylene. It has a non-crystalline character, a number average molecular weight Mn equal to about 9300 g / mol, and a polydispersity index Mw / Mn as high as 7.1. In addition, Rextac 2830 exhibits a melt viscosity of 3000 mPa·s at 190°C, and the thermal properties measured by DSC after aging for five days under room conditions are as follows: melting enthalpy of 22.1 J / g; peak melting temperature of 40°C and glass transition temperature of -24.1°C.
[0149] Koattro PB M 1500M, available from LyondellBasell (Netherlands), is considered to be a bimodal polymer composition of isotactic butene-1, synthesized over a metallocene catalyst, with a global number average molecular weight Mn equal to about 22800 g / mol and a global polydispersity index Mw / Mn equal to 2.3. This bimodal polymer composition is also considered to be composed of a copolymer of butene-1 and ethylene, with an ethylene content of about 13 mol % and a butene-1 homopolymer. In the polymerization step, once the butene-1 / ethylene copolymer is synthesized, it is thoroughly blended at the intermolecular level with the butene-1 homopolymer, also synthesized in the same reactor, in a ratio such that the global ethylene content in the final polymer composition is about 10 mol % (or about 5.3 wt %). The melt viscosity of Koattro PB M 1500M at 190°C is equal to 5630 mPa·s and the thermal properties measured by DSC after five days of aging under room conditions are as follows: melting enthalpy 34.3 J / g; peak melting temperature 110°C and glass transition temperature -41.4°C.
[0150] The hot melt formulation of Example 1 further comprises 23.7 wt% of Eastotac H-100L, a hydrogenated aliphatic hydrocarbon tackifying resin available from Synthomer (USA). The tackifier has a ring and ball softening point of 110°C and a number average molecular weight Mn equal to 410 g / mol.
[0151] Finally, the above disclosed adhesive also contained 2% by weight of the antioxidant Irganox 1010, available from BASF (Germany).
[0152] The adhesive formulation of Example 1 exhibits excellent adhesive properties and excellent processability. In fact, it can be processed without problems on a pilot line that runs at an extremely high speed of 250 m / min and reproduces the structure and working conditions of a real industrial production line for manufacturing absorbent hygiene products such as baby diapers. When its peel strength is tested according to the above-mentioned peel strength measurement method under such processing conditions, the adhesive formulation of Example 1 shows an optimal peel strength of up to 1.32 N / 50 mm, which clearly shows the excellent adhesive properties of this hot melt (Table 1).
[0153] The hot melt adhesive also has very good cohesive and mechanical properties, as measured at 23°C after five days of aging under room conditions, as 0.54 MJ / m 3 The toughness, the maximum stress (peak value) of the stress-elongation at break curve of 0.7 MPa, and the elongation at break of 157% are shown. In addition, the hot melt adhesive formulation of Example 1 also has the following properties: melt viscosity at 170°C is equal to 3880 mPa·s; ring and ball softening point is 103.8°C; rheological solidification temperature measured at time zero and at a cooling rate of 2°C / min and a frequency of 1 Hz is equal to 48°C; after aging for five days, the elastic modulus G' measured at 23°C and 1 Hz when the temperature is increased at a heating rate of 2°C / min is equal to 8.3 MPa.
[0154] Example 2
[0155] According to the invention, the following hot melt adhesive formulation was prepared by mixing its ingredients in the molten state at 170° C.:
[0156]
[0157] The hot melt adhesive formulation of Example 2 is based on a blend of the same butene-1-polymers already used in Example 1, obtained by slightly varying the ratio between the two polymer components. However, unlike Example 1, Example 2 does not contain any tackifier at all; in a general sense, it does not contain any low molecular weight non-polymer components (such as tackifiers, viscosity modifiers, waxes, etc., with a number average molecular weight of generally not more than 2500 g / mol) at all, and of course a small proportion of the antioxidant Irganox 1010.
[0158] As has been fully explained above, the lack of all low molecular weight components that are usually contained in hot melt adhesives, even in large quantities, gives this preparation additional, very special and beneficial properties. In particular, as explained in the previous context, this special preparation of the adhesive of Example 2 gives it the best stability of properties over time. In fact, the absence of all low molecular weight components that tend to separate from the preparation over time and migrate and ooze out of its surface ensures that all its main adhesive properties are abnormally constant over time. In addition, the lack of low molecular weight components from the preparation can also prevent the generation of bad odors, prevent possible effects of skin irritation, sensitization, and allergic or even toxic effects that are easy to occur when these exudates contact the user's skin.
[0159] Despite the absence of any tackifier or any viscosity modifier and plasticizer of low molecular weight, the formulation of Example 2 still has a relatively low melt viscosity, equal to 5750 mPa·s at 170° C., and can be easily processed without problems even on industrial production lines running at very high speeds (such as 250 m / min). In addition, even without a tackifier, this hot melt exhibits good adhesive properties, because when its peel strength is tested under the above conditions, it provides an excellent peel strength equal to 1.19 N / 50 mm (Table 1).
[0160] The absence of all low molecular weight components in Example 2 also further improves the already good cohesive and mechanical properties of Example 1. In fact, the adhesive formulation of Example 2 showed a toughness of 1.34 MJ / m at 23°C after five days of aging under room conditions. 3 The maximum stress (peak value) of the stress-elongation at break curve is equal to 1.4 MPa; the elongation at break is 165%.
[0161] The hot melt adhesive formulation of Example 2 also exhibited the following additional properties: a rheological solidification temperature equal to 73°C measured at time zero and at a cooling rate of 2°C / min and a frequency of 1 Hz; an elastic modulus G' equal to 18.8 MPa measured at 23°C and 1 Hz at a heating rate of 2°C / min after aging for five days.
[0162] Example 3
[0163] According to the invention, the following hot melt adhesive formulation was prepared by mixing its ingredients in the molten state at 170° C.:
[0164]
[0165] The hot melt adhesive formulation of Example 3 is based on a blend of two butene-1 polymers that are the same or similar to the two polymers used in the first two examples.
[0166] The main difference of Example 3 lies in the fact that it replaces the bimodal isotactic metallocene butadiene-1 polymer composition Koattro PB M 1500M with a similar bimodal isotactic metallocene butene-1 polymer composition Koattro PB M 8510M of similar chemical composition. Koattro PB M 8510M differs significantly from Koattro PB M 1500M in its higher number average molecular weight Mn, considered to be equal to 66700 g / mol. Other differences between Koattro PB M8510M and the previous Koattro product of lower molecular weight are the polydispersity index Mw / Mn equal to 2.1 and the much higher melt viscosity at 190°C, equal to 230000 mPa·s. Its thermal properties measured by DSC after five days of aging under room conditions are as follows: melting enthalpy of 38.2 J / g; peak melting temperature of 98.2°C and glass transition temperature of -36.4°C.
[0167] The use of Koattro PB M 8510M with a significantly higher molecular weight Mn further improves the cohesion and mechanical properties of the hot melt formulation compared to Koattro PB M 1500M, without affecting its very good processability even at a high speed of 250 m / min, and without compromising its excellent adhesive properties. In fact, the melt viscosity of the formulation of Example 3 is 5650 mPa·s and, when its peel strength is tested according to the method described above, it provides a very good peel strength equal to 0.98 N / 50 mm (Table 1).
[0168] After aging for five days under indoor conditions, the toughness of the hot melt in Example 3 measured as usual at 23°C was 5.84 MJ / m 3 ; The maximum stress (peak value) of its stress-elongation at break curve is equal to 0.9 MPa; and its elongation at break is extremely high, equal to 582%.
[0169] The hot melt adhesive formulation of Example 3 also exhibited the following additional properties: a ring and ball softening point of 105.7°C; a rheological setting temperature equal to 42°C measured at time zero and at a cooling rate of 2°C / min and a frequency of 1 Hz; and an elastic modulus G' equal to 15.0 MPa measured at 23°C and 1 Hz at a heating rate of 2°C / min after aging for five days.
[0170] Comparative Example
[0171] Comparative Example 1
[0172] The following comparative hot melt adhesive formulation has been prepared by mixing its ingredients in the molten state at 170°C:
[0173]
[0174] The hot melt adhesive formulation of Comparative Example 1 reproduces the same formulation as the previous Example 1 according to the invention, with the only difference that the bimodal polymer composition Koattro PB M 1500M of isotactic butene-1 previously synthesized on a metallocene catalyst with a polydispersity index Mw / Mn of 2.3 has been replaced by Koattro PB M 0801M, a unimodal isotactic, non-metallocene butene-1 homopolymer. Koattro PB M 0801M is believed to have a number average molecular weight Mn of about 20,500 g / mol and a polydispersity index of 4.9. It also exhibits a melt viscosity at 190°C equal to 47,000 mPa·s, a melting enthalpy after five days of aging of 78.3 J / g, a DSC peak melting temperature of 120.9°C and a glass transition temperature of -24.0°C.
[0175] When the peel strength is tested according to the method disclosed herein, the hot melt adhesive formulation of Comparative Example 1 has a melt viscosity of 7500 mPa·s at 170°C, showing an extremely low adhesive strength of only 0.15 N / 50 mm (Table 1). In addition, it exhibits a toughness of 8.15 MJ / m 3 The maximum stress (peak value) of the stress-elongation at break curve is 1.9 MPa, and the elongation at break is 131%; the ring and ball softening point is 118.3°C; the rheological solidification temperature measured at time zero and at a cooling rate of 2°C / min and a frequency of 1 Hz is equal to 55°C; after five days of aging, the elastic modulus G' measured at 23°C and 1 Hz at a heating rate of 2°C / min is equal to 19.3 MPa.
[0176] Comparative Example 2
[0177] The following comparative hot melt adhesive formulation has been prepared by mixing its ingredients in the molten state at 170°C:
[0178]
[0179] Furthermore, the hot melt adhesive formulation of Comparative Example 2 reproduces the same formulation of the previous Example 1 according to the invention, with the only difference that the previous unimodal non-isotactic butene-1 copolymer Rextac RT 2830 (which had a high polydispersity index Mw / Mn of 7.1, a melting enthalpy of only 22.1 J / g at five days of aging, a DSC peak melting temperature not higher than 80°C, more precisely equal to 40°C, etc.) has been replaced by a bimodal isotactic metallocene butene-1 polymer composition Koattro PB M 2500M, which is completely similar to the other main polymer component present in the formulation, namely Koattro PB M 1500M, differing only in terms of the number average molecular weight, equal to about 19600 g / mol, and a melt viscosity at 190°C of 3250 mPa·s, which is almost equal to the melt viscosity of Rextac RT 2830.
[0180] Furthermore, the bimodal polymer composition Koattro PBM 2500M of isotactic butene-1 synthesized on a metallocene catalyst has a polydispersity index Mw / Mn as low as 2.0, a melting enthalpy of 69.4 J / g at five days of aging, a DSC peak melting temperature well above 80° C., more precisely equal to 102.7° C., and a glass transition temperature of −26.7° C. It is also believed that its total ethylene comonomer content is about 7 mol% (i.e., about 3.6 wt%).
[0181] The formulation of Comparative Example 2 exhibited a peel strength of 0.66 N / 50 mm (Table 1), which is still significantly lower than the peel strengths exhibited by the first three examples according to the invention, but also significantly higher than the completely insufficient peel strength shown in the previous Comparative Example 1.
[0182] However, the biggest problem with Comparative Example 2 is that, in the molten state at 165° C., during application by slot die coating on a pilot line running at an industrial speed of 250 m / min, this formulation shows an unacceptably large amount of “build-up” phenomenon (also called “die-drool”). That is, as is well known to all those with an average expertise in the extrusion of polymers and polymer formulations, this very negative phenomenon consists in the fact that part of the extruded polymer formulation remains adhered to the metal of the extrusion head itself and accumulates in clumps of increasing weight and volume on the metal surfaces outside and around the extrusion orifice. These clumps of built-up material, which also begin to degrade due to the prolonged high temperature, occasionally and irregularly fall off the extrusion head, stick to the running substrate below, carrying these clumps of built-up material with them, while the build-up process starts anew. In this way, the quality of the finished product is irreparably damaged by this essentially chaotic and uncontrollable phenomenon, which is generally at an unacceptable level, both because the coating is very irregularly thin with non-uniform thickness, and because there are large chunks of adhesive in the random gaps, which are also severely degraded.
[0183] Therefore, the apparently relatively high average peel strength of 0.66 N / 50 mm recorded for Comparative Example 2 is most likely actually a "false positive result" because the very irregular coating of the extruded adhesive (with large clumps present) is scattered all over the place due to the clumps, skewing and falsifying the average reading of the overall average peel strength, with local strength peaks.
[0184] In addition, several mechanical and thermal properties of Comparative Example 2 are also inferior to those of the corresponding Example 1 according to the present invention, especially its elongation at break is only 85%, and its rheological solidification temperature measured at time zero and at a cooling rate of 2°C / min and a frequency of 1 Hz is unacceptably low, only equal to 26°C.
[0185] The hot melt adhesive formulation of Comparative Example 2 also exhibited the following additional properties: toughness of 4.5 MJ / m 3 The maximum stress (peak value) of the stress-elongation at break curve is equal to 3.3 MPa; the melt viscosity at 170°C is equal to 3500 mPa·s; the ring and ball softening point is 104.0°C; after five days of aging, the elastic modulus G' measured at 23°C and 1 Hz at a heating rate of 2°C / min is equal to 48.3 MPa.
[0186] Comparative Example 3
[0187] The following comparative hot melt adhesive formulation was prepared by mixing its ingredients in the molten state at 170°C:
[0188]
[0189] Likewise, the hot melt adhesive formulation of Comparative Example 3 conceptually reproduces the formulation of the preceding examples according to the invention. However, therein, the bimodal isotactic metallocene butene-1 polymer composition Koattro PB M 1500M or Koattro PB M 8510M has been replaced by the unimodal metallocene butene-1-polymer Tafmer PN-20300, which is considered to be a copolymer of butene-1, propylene and ethylene, containing about 30 mol % of butene-1, about 49 mol % of propylene and about 21 mol % of ethylene. Tafmer PN-20300 is also considered to have a number average molecular weight Mn equal to 72000 g / mol and a polydispersity index equal to 2.5. In addition, it has an unacceptably high melt viscosity of 810000 mPa·s at 190°C, a DSC melting enthalpy of 33.1 J / g at five days of aging, a very high peak melting temperature equal to 160.6°C, and a glass transition temperature of -28°C.
[0190] The hot melt of Comparative Example 3 proved to be completely unprocessable at all typical processing temperatures for processing hot melt adhesives, usually between 130° C. and 180° C. This was essentially due to its unacceptably high melt viscosity, for example up to 28,800 mPa·s at 170° C. Therefore, it was not possible to obtain any peel strength according to the peel strength method used herein.
[0191] In addition, the adhesive formulation of Comparative Example 3 also exhibited an unacceptably high ball and ring softening point of 149.4°C. Its toughness after aging for five days was equal to 6.05 MJ / m 3 The maximum stress (peak value) of the stress-elongation at break curve is 0.9 MPa, and the elongation at break is 596%; the rheological solidification temperature measured at time zero and at a cooling rate of 2°C / min and a frequency of 1 Hz is equal to 88°C; after five days of aging, the elastic modulus G' measured at 23°C and 1 Hz at a heating rate of 2°C / min is equal to 8.5 MPa.
[0192] Table 1 - Peel Strength
[0193] (measured according to the method described above)
[0194]
Claims
1. A hot melt adhesive, characterized in that: The hot melt adhesive comprises a polymer blend of at least two butene-1 polymers A) and B), the blend comprising: A) from 5% to 95% by weight, relative to the total weight of the blend, of at least one non-isotactic butene-1 copolymer having a polydispersity index Mw / Mn of not less than 3.5 and having a unimodal composition, the copolymer consisting of butene-1 and one or more α-olefins chosen from ethylene, propylene and C5 to C12 α-olefins, the copolymer also having a content of copolymerized comonomer of not less than 20 mol %, a viscosity at 190° C. of from 1000 mPa·s to 200000 mPa·s, and also having the following thermal properties measured by DSC after aging for five days under room conditions: - melting enthalpy is not more than 40 J / g, preferably not more than 35 J / g, more preferably not more than 30 J / g; - Peak melting temperature is not higher than 80°C; - Glass transition temperature Tg is not higher than -10°C; B) from 95% to 5% by weight, relative to the total weight of the blend, of at least one isotactic butene-1 polymer composition with a global polydispersity index Mw / Mn of less than 3.5 and having a bimodal composition, the bimodal polymer composition comprising: B1) 10 to 90% by weight of a butene-1 copolymer with one or more comonomers selected from ethylene, propylene and α-olefins having a carbon number equal to or greater than 5, said copolymer B1) having a content of copolymerized comonomers less than 20 mol % and a polydispersity index Mw / Mn less than 3.5; B2) 90% to 10% by weight of a butene-1 homopolymer or butene-1 copolymer having one or more comonomers selected from ethylene, propylene and α-olefins having 5 or more carbon atoms, said homopolymer or copolymer B2) having a content of copolymerized comonomers of not more than 5 mol % and a polydispersity index Mw / Mn of less than 3.5; The isotactic butene-1 polymer composition has a bimodal composition, a viscosity at 190° C. of 1000 to 300000 mPa·s, and also has the following thermal properties measured by DSC after aging for five days under room conditions: - a melting enthalpy greater than 20 J / g, preferably greater than 25 J / g, more preferably greater than 30 J / g, - Peak melting temperature above 90°C, - The glass transition temperature Tg is not higher than -20°C.
2. The hot melt adhesive according to claim 1, characterized in that The isotactic butene-1 polymer composition B) has a global polydispersity index Mw / Mn of less than 3.5 and has a bimodal composition and comprises two polymers B1) and B2), the weight ratio between components B1) and B2) of the isotactic butene-1 polymer composition B) being such that the global content of copolymerized comonomers other than butene-1, relative to the sum of B1) plus B2), is less than 20 mol %, preferably from 3 mol % to 18 mol %.
3. The hot melt adhesive according to claim 1, characterized in that The non-isotactic butene-1 copolymer A) has a polydispersity index Mw / Mn of not less than 3.5 and has a monomodal composition, a number average molecular weight Mn of not more than 30,000 g / mol and preferably not more than 20,000 g / mol.
4. The hot melt adhesive according to claims 1 and 2, characterized in that The isotactic butene-1 composition B) has a polydispersity index of less than 3.5 and a bimodal composition and comprises two polymers B1) and B2) with a number average molecular weight Mn of not more than 150,000 g / mol, preferably not more than 100,000 g / mol, more preferably not more than 80,000 g / mol.
5. The hot melt adhesive according to any one of the preceding claims 1 to 4, characterized in that The polymer blend of at least two butene-1 polymers A) and B) comprises 10 to 95 wt% of a non-isotactic butene-1 copolymer A) and 5 to 60 wt% of a bimodal isotactic butene-1 polymer composition B).
6. The hot melt adhesive according to any one of the preceding claims 1 to 5, characterized in that The weight ratio between A) and B) in the polymer blend of at least two butene-1 polymers A) and B) is greater than 1.
7. The hot melt adhesive according to any one of the preceding claims 1 to 6, characterized in that The polymer blend of at least two butene-1 polymers A) and B) further comprises from 0% to 30% by weight of at least one butene-1 homopolymer or butene-1 copolymer with one or more α-olefins selected from ethylene, propylene and C5 to C12 olefins, said homopolymer or copolymer C1) having a content of copolymerized comonomers of less than 20 mol % and a polydispersity index greater than 3.5, a melting enthalpy after five days greater than 30 J / g, a melting peak temperature greater than 80° C. and a glass transition temperature Tg not greater than −10° C., the thermal properties being measured by DSC.
8. The hot melt adhesive according to any one of the preceding claims 1 to 6, characterized in that The polymer blend of at least two butene-1 polymers A) and B) further comprises from 0% to 30% by weight of at least one butene-1 homopolymer or butene-1 copolymer with one or more α-olefins selected from ethylene, propylene and C5 to C12 olefins, said homopolymer or copolymer C2) having a content of copolymerized comonomer of not less than 20 mol % and a polydispersity index of less than 3.5, a melting enthalpy after five days of not more than 30 J / g, a melting peak temperature of not higher than 90° C. and a glass transition temperature Tg of not higher than −20° C., the thermal properties being measured by DSC.
9. The hot melt adhesive according to claim 7 or 8, characterized in that: The butene-1 homopolymer or copolymer C1) or C2) has a unimodal composition.
10. The hot melt adhesive according to any one of the preceding claims 1 to 9, characterized in that The hot melt adhesive also comprises 0% to 30% by weight of one or more butene-1-free polymers (homopolymers, copolymers, and blends thereof).
11. The hot melt adhesive according to claim 10, characterized in that The butene-1-free polymer is a polyolefin.
12. The hot melt adhesive according to claims 10 and 11, characterized in that The butene-1-free polymer is a propylene homopolymer, a copolymer of ethylene and propylene, or a copolymer of propylene and C5 to C12 α-olefin, or a copolymer of propylene and ethylene and C5 to C12 α-olefin.
13. The hot melt adhesive according to any one of the preceding claims 10 to 12, characterized in that The polyolefin comprises hexene.
14. The hot melt adhesive according to any one of the preceding claims 10 to 12, characterized in that The polyolefin is a copolymer of propylene and ethylene having a heterophasic structure.
15. The hot melt adhesive according to any one of the preceding claims 1 to 14, characterized in that The sum of all polymers listed in the claims constitutes from 5% to 99.5% by weight of the total hot melt adhesive.
16. The hot melt adhesive according to any one of the preceding claims 1 to 15, characterized in that The hot melt adhesive also contains 0% to 70% by weight of at least one tackifying resin.
17. The hot melt adhesive according to claim 16, characterized in that The tackifying resin is selected from: non-hydrogenated, partially hydrogenated or fully hydrogenated aliphatic hydrocarbon resins; non-hydrogenated, partially hydrogenated or fully hydrogenated aromatic hydrocarbon resins; non-hydrogenated, partially hydrogenated or fully hydrogenated aliphatic-aromatic hydrocarbon resins; non-hydrogenated, partially hydrogenated or fully hydrogenated polyterpene resins and modified polyterpene resins; non-hydrogenated, partially hydrogenated or fully hydrogenated rosin and its esters; and blends thereof.
18. The hot melt adhesive according to claims 16 and 17, characterized in that The tackifying resin or the blend of tackifying resins has a ring and ball softening temperature of 5°C to 160°C, preferably not less than 70°C.
19. The hot melt adhesive according to any one of the preceding claims 1 to 18, characterized in that The hot melt adhesive also comprises 0% to 40% by weight of at least one viscosity modifier or blend of viscosity modifiers that is not solid at room temperature (23°C).
20. The hot melt adhesive according to claim 19, characterized in that The viscosity modifier that is not solid at room temperature or the blend of the modifier is selected from: paraffinic mineral oil; naphthenic mineral oil; paraffinic hydrocarbons and cycloalkanes that are not solid at room temperature and their blends; oligomers and polymers of C2 to C20 polyolefins that are not solid at room temperature and their co-oligomers and copolymers that are not solid at room temperature; viscosity modifiers that are not solid at room temperature composed of esters such as phthalates, benzoates, sebacates, citrates, tartrates, etc.; vegetable oils; natural and synthetic fats; and their blends.
21. The hot melt adhesive according to claim 20, characterized in that The polydispersity index of oligomers and polymers of C2 to C20 polyolefins that are not solid at room temperature and co-oligomers and copolymers thereof that are not solid at room temperature is not greater than 3.5, preferably not greater than 2.
5.
22. The hot melt adhesive according to any one of the preceding claims 1 to 21, characterized in that The hot melt adhesive comprises 0% to 10% by weight, preferably 0% to 5% by weight, of a wax or a blend of waxes.
23. The hot melt adhesive according to claim 22, characterized in that The wax contains more than 50 mol % of ethylene or propylene, and has a viscosity of not more than 2000 mPa·s at 190° C.
24. The hot melt adhesive according to claim 23, characterized in that The waxes containing greater than 50 mole % ethylene or propylene are modified with maleic anhydride.
25. The hot melt adhesive according to any one of the preceding claims 1 to 24, characterized in that The hot melt adhesive contains up to 10% by weight of at least one stabilizer, such as antioxidants, anti-ultraviolet light stabilizers, and blends thereof.
26. The hot melt adhesive according to any one of the preceding claims 1 to 25, characterized in that The hot melt adhesive contains 60% to 99.5% by weight of polymer.
27. The hot melt adhesive according to any one of the preceding claims 1 to 26, characterized in that The hot melt adhesive contains the sum of tackifying resin, viscosity modifier and wax in an amount of 0 to 35 wt %, preferably 0 to 25 wt % and more preferably 0 to 15 wt %.
28. The hot melt adhesive according to any one of the preceding claims 1 to 27, characterized in that The hot melt adhesive comprises 0 to 10 wt % of at least one additional ingredient selected from mineral fillers, pigments, dyes, fragrances, surfactants, antistatic agents and blends thereof.
29. The hot melt adhesive according to any one of the preceding claims 1 to 28, characterized in that The Brookfield viscosity of the hot melt adhesive at 170° C. is not greater than 20,000 mPa·s, preferably not greater than 15,000 mPa·s.
30. The hot melt adhesive according to any one of the preceding claims 1 to 29, characterized in that The ring and ball softening temperature of the hot melt adhesive is not higher than 135°C, preferably not higher than 120°C.
31. The hot melt adhesive according to any one of the preceding claims 1 to 30, characterized in that After aging for five days under indoor conditions, the toughness of the stress-elongation-at-break curve of the hot melt adhesive measured at 23°C and a frequency of 0.1 Hz is not less than 0.1 MJ / m 3 .
32. The hot melt adhesive according to claim 31, characterized in that The maximum stress (peak value) of the stress-breaking elongation curve of the hot melt adhesive at 23° C. and 0.1 Hz is not less than 0.15 MPa.
33. The hot melt adhesive according to claims 31 and 32, characterized in that The hot melt adhesive has an elongation at break of not less than 50% at 23° C. and 0.1 Hz.
34. The hot melt adhesive according to any one of the preceding claims 1 to 33, characterized in that The rheological solidification temperature Tx of the hot melt adhesive measured at a frequency of 1 Hz at time zero and when cooled at a cooling rate of 2° C. / min is not less than 30° C.
35. The hot melt adhesive according to any one of the preceding claims 1 to 34, characterized in that After aging for five days under room conditions, when the elastic modulus is measured at 23° C. and 1 Hz at a heating rate of 2° C. / min, the hot melt adhesive has an elastic modulus G′ of not less than 0.2 MPa.
36. A glued structure, comprising: - a first substrate; - a second substrate; - The hot melt adhesive of any one of the preceding claims 1 to 35, which bonds the first substrate to the second substrate and when 0.5 g / m 2 Up to 50g / m 2 When applied at a basis weight of 1000 Å, the hot melt adhesive imparts to the bonded structure a peel strength greater than 0.25 N per 50 mm width measured after aging for five days under room conditions.
37. The glued structure according to claim 36, characterized in that At least one of the two substrates is a porous or fibrous substrate or a nonwoven fabric or a perforated film having a two-dimensional or three-dimensional structure.
38. An absorbent sanitary product, characterized in that: The absorbent hygiene article comprises the hot melt adhesive according to any one of the preceding claims 1 to 35.
39. An absorbent sanitary product, characterized in that: The absorbent hygiene article comprises the glued structure according to any one of the preceding claims 36 to 37.
40. The article according to claim 38 or 39, characterized in that The articles are absorbent diapers for infants or children, training pants for toddlers, absorbent diapers for incontinent adults and absorbent articles for feminine hygiene.
41. An absorbent sanitary article according to any one of claims 38 to 40, characterized in that The hot melt adhesive is used for at least one of the following purposes: i) a general construction adhesive for the entire article; ii) for gluing elastic components (threads, belts, films or elastic plates, etc.); iii) for consolidating / fixing the absorbent layer of the absorbent sanitary article and ensuring its integrity during use; iv) for gluing perforated films with two-dimensional or three-dimensional structures; v) for gluing two nonwoven fabrics or two plastic films to each other, or for gluing a nonwoven fabric to a plastic film.
42. An article comprising the hot melt adhesive according to any one of claims 1 to 35, characterized in that: The article is an absorbent pad or sheet or surgical laminate for medical use, or a product for covering and protecting wounds.
43. An article comprising the hot melt adhesive according to any one of claims 1 to 35, characterized in that: The article is a mattress or a component thereof.
44. An article comprising the hot melt adhesive according to any one of claims 1 to 35, characterized in that: The supplies are packaging materials.
Citation Information
Patent Citations
Hot melt adhesive containing butene-1 polymers
EP0314495A2
Butene-1 polymer composition having a high melt flow rate
EP3266824A1
Butene-1 polymer composition having a high melt flow rate
EP3266825A1
Hot melt poly(butylene / ethylene) adhesives
US4568713A
Stanchion
US456871A